Powder and preparation method thereof, target material and preparation method thereof, molybdenum-silicon compound film, mask plate and preparation method of semiconductor device
By preparing high-purity and low-oxygen content MoSix powder, the problem of uneven texture of existing molybdenum silicon target materials is solved, the uniform texture of the molybdenum silicon compound film is achieved and the light transmittance is stabilized, the contrast and resolution of the phase shift mask plate is improved, and the needs of the fine electronics industry are met.
Patent Information
- Application Number
- CN202510061620.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing molybdenum silicon targets have low purity, high oxygen content or uneven microstructure, resulting in uneven texture of the molybdenum silicon compound film obtained by sputtering, unstable light transmittance, and inaccurate phase difference, which cannot meet the requirements of the fine electronics industry.
A method for preparing MoSix powder is provided. By mixing the atomic ratio of molybdenum:silicon is 1: x (x≥2), sintering and crushing into powder with suitable particle size in vacuo to obtain MoSix powder with high purity, low oxygen content and small particle size, and is used to prepare molybdenum silicon target materials with high purity and low oxygen content.
The MoSix powder produced by this method can be used to prepare a molybdenum silicon compound film with uniform texture and low oxygen content, improve the product yield of the phase shift mask plate, significantly reduce the gray shaded area of the patterned graphics, improve the contrast and resolution of the graphics, and meet the application needs of the fine electronics industry.
Smart Images

Figure CN119461381B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application belong to the field of semiconductor preparation, and in particular, relate to a powder and a preparation method thereof, a target material and a preparation method thereof, a molybdenum-silicon compound film, a mask plate, and a preparation method of a semiconductor device. Background Art
[0002] The mask is an important semiconductor material. It is a common graphic master used in the patterning development process in micro-nano processing technology. As a carrier of graphic information, it transfers the graphic to the exposed silicon wafer through the exposure process, thereby realizing the transfer of the graphic. When the wafer production process reaches 0.18μm, the contrast of the overall graphic will be reduced due to the scattering of the graphic edge, making the graphic no longer black and white, and containing many gray shadow areas, resulting in unsatisfactory patterning effect. In order to improve the contrast of the graphic, the industry often uses phase shift mask (PSM) technology, which uses the interference offset of the graphic edge to improve the contrast through the phase shift mask.
[0003] The phase shift film formed by molybdenum silicon compound is one of the important components of the phase shift mask. The molybdenum silicon compound phase shift film is usually formed by bombarding the molybdenum silicon target material with magnetron sputtering to make the molybdenum silicon compound detach and deposit on the substrate. However, due to the low purity, high oxygen content or uneven microstructure of the currently produced molybdenum silicon target material, the molybdenum silicon compound film obtained by sputtering is uneven in texture, unstable in light transmittance for exposure, and inaccurate in phase difference, resulting in an unsatisfactory phase shift effect and unable to meet the requirements of the precision electronics industry. The quality of the molybdenum silicon target material mainly depends on the quality of the molybdenum silicide raw material. Therefore, it is necessary to provide a high-purity, low-oxygen molybdenum silicide material. Summary of the invention
[0004] In view of this, the present application embodiment provides a MoSi x A method for preparing a powder, which can produce MoSi with high purity, low oxygen content and small particle size x Powder, MoSi x The powder can be used to prepare high-purity, low-oxygen-content, and uniform microstructured molybdenum-silicon target materials, which can then be sputtered to obtain a uniform, dense, and low-oxygen-content molybdenum-silicon compound film. The molybdenum-silicon compound film can then be used to prepare a phase-shift film with stable light transmittance and accurate phase difference for exposure, which is beneficial for forming high-contrast, high-resolution development patterns in the semiconductor preparation process to meet the application needs of the precision electronics industry.
[0005] In a first aspect, the present application embodiment provides a MoSi x The method for preparing the powder comprises:
[0006] Molybdenum powder and silicon powder are mixed according to the atomic ratio of molybdenum to silicon of 1:x to obtain a molybdenum-silicon mixture; wherein x≥2;
[0007] The molybdenum-silicon mixture is placed in a vacuum sintering device for vacuum sintering to obtain MoSi x The sintering temperature of the vacuum sintering is 1150°C-1410°C;
[0008] The MoSi x The block is crushed to a particle size of 2 μm-20 μm with a D50 particle size of 2 μm-20 μm and [(D90-D10) / D50]≤2.5 to obtain MoSi x Powder.
[0009] The MoSi provided in the embodiments of the present application x The powder preparation method is to sinter under vacuum conditions at 1150℃-1410℃, which not only ensures the full alloying of the molybdenum-silicon mixture, and the sintered product contains no other molybdenum-silicon compound impurity phase except MoSi2 phase, but also can remove the combined oxygen and free oxygen in the molybdenum-silicon mixture, thereby reducing the final MoSi x The oxygen content of the powder; in addition, by x The block is crushed to a particle size of 2μm-20μm with a D50 particle size of [(D90-D10) / D50]≤2.5, which can obtain the smallest possible powder particle size while taking into account the lower oxygen content; thus, MoSi with high purity, low oxygen content and small particle size can be finally obtained. x MoSi powder prepared by the preparation method of the present application x The powder can be used to prepare a high-purity, low-oxygen, microstructured molybdenum-silicon target material, and then a dense and uniform molybdenum-silicon compound film can be deposited to improve the product yield of the phase-shift mask. The phase-shift film made of the molybdenum-silicon compound film has a stable light transmittance for exposure and an accurate phase difference, which can significantly reduce the gray shadow area of the patterned graphics and improve the overall contrast of the graphics, thereby facilitating the formation of a high-contrast, high-resolution development pattern in the semiconductor preparation process and improving the performance of semiconductor devices. The MoSi x The powder preparation method has a simple process and is easy to realize industrial production.
[0010] In the embodiment of the present application, the vacuum degree of the vacuum sintering is 1×10 -3 Pa ~1Pa, vacuum is continuously drawn during the vacuum sintering process, and the vacuum sintering includes keeping the temperature at the sintering temperature for 1h~5h.
[0011] In the embodiment of the present application, during the vacuum sintering process, the temperature is increased to the sintering temperature at a heating rate of 1° C. / min to 10° C. / min.
[0012] In the implementation manner of the present application, the purity of the molybdenum powder is ≥99.999%, and the particle size of the Fisher particle size D50 is 1μm~10μm; the purity of the silicon powder is ≥99.999%, and the particle size of the laser particle size D50 is 10μm~100μm.
[0013] In the implementation manner of the present application, the mixing is performed under a protective atmosphere.
[0014] In some embodiments of the present application, the MoSi x The blocks are crushed to particles with a D50 particle size of 5 μm-12 μm, and [(D90-D10) / D50]≤1.2.
[0015] In the embodiment of the present application, the crushing method includes any one or more combinations of ball milling, vibration milling, air flow milling, and impact milling.
[0016] In the implementation manner of the present application, the MoSi x The purity of the powder is ≥99.999%, and the oxygen content is ≤1500ppm.
[0017] In the implementation manner of the present application, the MoSi x The carbon content of the powder is ≤200ppm, the iron content is ≤5ppm, the aluminum content is ≤5ppm, the nickel content is ≤5ppm, and the copper content is ≤5ppm.
[0018] In a second aspect, the present application embodiment provides a MoSi x The powder adopts the MoSi x The powder is prepared by the method for preparing the powder.
[0019] In a third aspect, the present application provides a method for preparing a molybdenum-silicon target, comprising:
[0020] Using the MoSi described in the first aspect of the present application x MoSi powder preparation method x Powder;
[0021] Using the MoSi x The powder is pressed into shape to obtain a molybdenum-silicon target.
[0022] In the embodiment of the present application, the pressing molding of the molybdenum-silicon target material includes any one of isostatic pressing and hot pressing.
[0023] In a fourth aspect, an embodiment of the present application further provides a molybdenum-silicon target material, which is prepared using the method for preparing the molybdenum-silicon target material described in the third aspect of the embodiment of the present application.
[0024] In a fifth aspect, an embodiment of the present application provides a molybdenum-silicon compound film, which is obtained by physical vapor deposition using the molybdenum-silicon target material described in the fourth aspect of the embodiment of the present application.
[0025] In the sixth aspect, an embodiment of the present application provides a phase-shift mask plate, which includes a substrate and a phase-shift film and a light-shielding film stacked on a surface of one side of the substrate, the phase-shift film includes the molybdenum-silicon compound film described in the fifth aspect of the present application, and the phase-shift mask plate includes a blank phase-shift mask plate or a phase-shift mask plate with a preset pattern.
[0026] In a seventh aspect, an embodiment of the present application further provides a method for preparing a semiconductor device, comprising:
[0027] The phase-shift mask with a preset pattern described in the sixth aspect of the embodiment of the present application is placed on the semiconductor substrate to be patterned;
[0028] After exposure, the preset pattern on the phase-shift mask having the preset pattern is transferred to the semiconductor substrate to be patterned. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The X-ray diffraction analysis (XRD) result diagram of MoSi2 powder in Examples 1-4 and Comparative Examples 1-2 of the present application;
[0030] Figure 2A This is a scanning electron microscope (SEM) image of the molybdenum-silicon target prepared in Example 4;
[0031] Figure 2B This is an EDS energy spectrum scan of the molybdenum silicon target prepared in Example 4;
[0032] Figure 3A This is a scanning electron microscope (SEM) image of the molybdenum silicon target prepared in Comparative Example 2;
[0033] Figure 3B This is the EDS energy spectrum scan of the molybdenum silicon target prepared in Comparative Example 2. DETAILED DESCRIPTION
[0034] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.
[0035] Unless otherwise specified, the raw materials used in the examples of this application are all commercially available products.
[0036] Phase shift mask (PSM) technology is a resolution enhancement technology that uses both the intensity and phase of light to form an image and obtain a higher resolution. Its basic principle is to change the mask structure so that the light waves passing through adjacent light-transmitting areas produce a 180° phase difference. The two will cause destructive interference in a specific area on the image plane, reducing the light intensity of the dark field in the light field and increasing the light field in the bright area, so as to improve the contrast of the patterned graphics and the resolution.
[0037] The phase-shift mask is generally composed of a substrate, a phase-shift film, a light-shielding film and other film structures. The phase-shift film usually has a phase difference of 175°~185° for the exposed light, and a transmittance of about 6%~30%. At present, the mainstream solution is to use a molybdenum-silicon compound film as a phase-shift film to prepare a phase-shift mask. The specific operation can be: make a molybdenum-silicon compound into a molybdenum-silicon target material, bombard the molybdenum-silicon target material by magnetron sputtering, and bombard the molybdenum-silicon target material with high-speed argon ions to separate the molybdenum-silicon compound from the target material and deposit it on the substrate to form a molybdenum-silicon compound film. The quality of the molybdenum-silicon target material directly affects the quality of the patterned graphics obtained using the phase-shift mask. However, the molybdenum-silicon target materials currently produced on the market have low purity and high oxygen content, which makes it difficult to meet the requirements of the phase-shift mask for the quality of the molybdenum-silicon target material. The quality of molybdenum silicon target mainly depends on the quality of the raw material of molybdenum silicon compound that forms the target. High-purity, low-oxygen content raw material of molybdenum silicon compound is a prerequisite for the preparation of high-quality molybdenum silicon target, and it also plays a vital role in the quality of phase shift mask. If the oxygen content in the raw material of molybdenum silicon compound is high, it will prevent the subsequent sintering densification of the target, the porosity will be large, and the rolling performance will be poor. During the sputtering process, a large amount of target particles will splash, the sputtering coating quality will be poor, the film texture will be uneven, the light transmittance for exposure will be unstable and the phase difference will be inaccurate, resulting in unsatisfactory phase shift effect, and it is impossible to obtain high-resolution, high-contrast patterned graphics, which will lead to a decrease in the yield rate of semiconductor devices.
[0038] In view of this, the present application embodiment provides a MoSi x A method for preparing a powder, which can produce MoSi with high purity, low oxygen content and small particle size x Powder, MoSi x The powder can be used to prepare high-purity, low-oxygen-content, and uniform microstructured molybdenum-silicon target materials, which can then be sputtered to obtain a uniform, dense, and low-oxygen-content molybdenum-silicon compound film. The molybdenum-silicon compound film can then be used to prepare a phase-shift film with stable light transmittance and accurate phase difference for exposure, which is beneficial for forming high-contrast, high-resolution development patterns in the semiconductor preparation process to meet the application needs of the precision electronics industry.
[0039] The present application embodiment provides a MoSi x The method for preparing the powder comprises the following steps:
[0040] S101, mixing molybdenum powder and silicon powder according to the atomic ratio of molybdenum to silicon of 1:x to obtain a molybdenum-silicon mixture; wherein x≥2;
[0041] S102, placing the molybdenum-silicon mixture obtained in S101 in a vacuum sintering device for vacuum sintering to obtain MoSi x Block; the sintering temperature of vacuum sintering is 1150℃-1410℃;
[0042] S103, the MoSi obtained in S102 x The block is crushed to a particle size of 2 μm-20 μm at D50, and [(D90-D10) / D50]≤2.5 to obtain MoSi x Powder.
[0043] The MoSi provided in the embodiments of the present application x The powder preparation method is to sinter under vacuum conditions at 1150℃-1410℃, which not only ensures the full alloying of the molybdenum-silicon mixture, and the sintered product contains no other molybdenum-silicon compound impurity phase except MoSi2 phase, but also can remove the combined oxygen and free oxygen in the molybdenum-silicon mixture, thereby reducing the final MoSi x The oxygen content of the powder; in addition, by x The block is crushed to a particle size of 2μm-20μm with a D50 particle size of [(D90-D10) / D50]≤2.5, which can obtain the smallest possible powder particle size while taking into account the lower oxygen content; thus, MoSi with high purity, low oxygen content and small particle size can be finally obtained. x MoSi powder prepared by the preparation method of the present application x The powder can be used to prepare a high-purity, low-oxygen, microstructured molybdenum-silicon target material, and then a dense and uniform molybdenum-silicon compound film can be deposited to improve the product yield of the phase-shift mask. The phase-shift film made of the molybdenum-silicon compound film has a stable light transmittance for exposure and an accurate phase difference, which can significantly reduce the gray shadow area of the patterned graphics and improve the overall contrast of the graphics, thereby facilitating the formation of a high-contrast, high-resolution development pattern in the semiconductor preparation process and improving the performance of semiconductor devices. The MoSi x The powder preparation method has a simple process and is easy to realize industrial production.
[0044] In step S101, in some embodiments, the purity of molybdenum powder and silicon powder can be ≥99.999%, for example, but not limited to 99.9995%, 99.9997%, 99.9999%, the purity of the raw materials largely determines the purity of the final product, so the higher the purity of the raw materials of molybdenum powder and silicon powder, the better. The Fisher particle size D50 of the molybdenum powder can be 1μm~10μm, for example, but not limited to 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm. The laser particle size D50 of the silicon powder can be 10μm~100μm, for example, but not limited to 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm, 70μm, 80μm, 90μm, and 100μm.
[0045] D50 particle size: The particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, also called median particle size or median particle size.
[0046] In the embodiment of the present application, the mixing process may include: putting the weighed molybdenum powder and silicon powder into a mixing barrel, installing the mixing barrel on a mixer, filling the mixing barrel with protective gas, adding a medium ball, starting the mixer, and mixing the molybdenum powder and silicon powder to obtain MoSi x Mixture.
[0047] In the embodiment of the present application, the atomic ratio of molybdenum to silicon is 1:x, and x can be, but is not limited to, 2, 4, 7, 9, or 12. Molybdenum powder and silicon powder can be obtained according to the molybdenum-to-silicon ratio requirement of the molybdenum-to-silicon target.
[0048] In the embodiment of the present application, the protective gas filled into the mixing barrel is an anti-oxidation gas, such as nitrogen and / or an inert gas. The inert gas may be, for example, argon. Its purpose is to isolate the mixed powder from the air and prevent the silicon powder and molybdenum powder from coming into contact with oxygen and being oxidized during mixing, thereby helping to control the oxygen content of the molybdenum-silicon mixture at a lower level.
[0049] In some embodiments of the present application, the entire mixing process is carried out under closed conditions, which can prevent dust or impurities in the air from entering the mixer and affecting the purity of the mixed powder, and can also prevent oxygen in the air from oxidizing the molybdenum silicon powder, which is conducive to obtaining MoSi with high purity and low oxygen content. x powder.
[0050] In the embodiment of the present application, the mixer can be, but is not limited to, a ball mill, and the speed of the ball mill can be 5r / min~30r / min; the mixing time can be 2h~5h. A 20min~30min interval can be used for cooling down after each mixing hour. Appropriate ball milling speed and ball milling time are conducive to uniform distribution of molybdenum powder and silicon powder in the molybdenum silicon mixture, and are also conducive to avoiding the crushing of the molybdenum silicon mixture powder and thus reducing the particle size of some powder particles, resulting in uneven powder particle size, thereby affecting the subsequent MoSi x Powder formation and quality.
[0051] In the embodiment of the present application, the dielectric ball can be, but is not limited to, a zirconium oxide ball, a molybdenum ball, a silicon ball, or a silicon nitride ball. The dielectric ball is relatively stable in nature and is not easily worn during the friction of the mixed material, nor does it affect the mixed raw materials. The mass ratio of the dielectric ball to the molybdenum-silicon mixed material can be (1-10):1, and the diameter of the dielectric ball can be 5μm-25μm.
[0052] In the embodiment of the present application, the powder mixing method is dry mixing, and no solvent is added during the mixing process. Dry mixing can prevent the molybdenum powder and the silicon powder from adhering to the dead corner or the machine wall and not contacting the medium ball, which is conducive to the uniform mixing of the molybdenum powder and the silicon powder, and is also conducive to stabilizing the molybdenum-silicon atomic ratio, and obtaining MoSi x Powder, especially when the atomic ratio of molybdenum to silicon is 1:2, is conducive to ensuring that the subsequently generated molybdenum-silicon product has only a single phase of MoSi2. At the same time, it can also avoid the loss of molybdenum powder and silicon powder raw materials during the mixing process and realize the full utilization of raw materials.
[0053] In step S102, during the vacuum sintering process, the vacuum sintering equipment may be evacuated to a vacuum degree of 1×10 -3 Pa ~1Pa, for example 1×10 -3 Pa, 1×10 -2 Pa, 1×10 -1 Pa, 1Pa, the vacuum environment can effectively prevent the molybdenum-silicon mixture from oxidizing during the sintering process, and is also conducive to degassing (SiO) and reducing oxygen during the sintering process. In the specific implementation of the present application, the temperature rise program is started after the vacuum is evacuated to a stable vacuum degree. The vacuum sintering equipment can be a vacuum sintering furnace. The vacuum sintering process can be continuously evacuated to discharge the gas SiO generated during the sintering process.
[0054] In the embodiment of the present application, during the vacuum sintering process, the temperature can be raised to the sintering temperature at a heating rate of 1°C / min to 10°C / min. The heating rate can be, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. In some embodiments of the present application, the heating rate of 0°C-1000°C is 5°C / min-10°C / min, and the heating rate above 1000°C is less than 5°C / min. Maintaining a suitable heating rate is conducive to promoting the full occurrence of the reaction and the removal of oxygen, and can also better avoid the uneven temperature inside the furnace and the furnace wall due to the lack of time for the furnace temperature in the vacuum sintering furnace to diffuse, resulting in furnace temperature deviation, and making the reaction uneven.
[0055] During the heating process, heat is gradually transferred from the outside to the inside of the molybdenum-silicon mixture, and the moisture in it is discharged under vacuum conditions. As the temperature of the molybdenum-silicon mixture rises and the heat increases, the molybdenum atoms and silicon atoms diffuse with each other. When a certain temperature is reached, a chemical reaction begins to occur between molybdenum and silicon.
[0056] In the embodiments of the present application, the end temperature of the heating, that is, the sintering temperature of the vacuum sintering, can be 1150° C.-1410° C. In some embodiments of the present application, the end temperature of the heating can be, for example but not limited to, 1150° C., 1180° C., 1190° C., 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., 1410° C.
[0057] In the present application, the holding time at the sintering temperature can be 1h-5h, which can be but not limited to 1h, 2h, 3h, 4h, 5h. The appropriate holding time can not only ensure that the heat is fully diffused in the molybdenum-silicon mixture, but also promote all the molybdenum and silicon to fully react and transform into MoSi2 single phase, without the existence of single substance Mo, avoid the generation of other molybdenum-silicon compound impurities, and improve the utilization rate of raw materials.
[0058] In some embodiments of the present application, the molybdenum-silicon mixture is sintered into MoSi x The alloy reaction mainly takes place during the period of heat preservation at the sintering temperature. During this process, as the heat continues to increase, molybdenum atoms and silicon atoms diffuse with each other, and a chemical reaction occurs between molybdenum and silicon, which are tightly combined through chemical bonds. The temperature control at this stage is crucial to the composition phase and oxygen content of the final sintered product.
[0059] The inventors have found through a large number of experiments that molybdenum and silicon can form different reaction products, namely, molybdenum silicide (Mo3Si), molybdenum silicide (Mo5Si3), and molybdenum disilicide (MoSi2), under different temperature conditions. Specifically:
[0060] When 900℃<furnace temperature t<1100℃, the reaction product is only Mo3Si, and the reaction process is as follows:
[0061] 3Mo ( s )+Si ( s )=Mo3Si (s )(1)
[0062] When 1100℃≤furnace temperature t<1150℃, the reaction products include Mo3Si and Mo5Si3, and the reaction process is as follows:
[0063] 3Mo ( s )+Si ( s )=Mo3Si ( s )(1)
[0064] 5Mo3O ( s )+4Si ( s )=3Mo5Si3( s )(2)
[0065] 5Mo ( s)+3Si ( s )=Mo5Si3( s )(3)
[0066] When the furnace temperature is 1150℃≤t<1410℃, the Mo3Si and Mo5Si3 generated in the previous low temperature stage are converted into the target product MoSi2, and the reaction process is as follows:
[0067] 3Mo ( s )+Si ( s )=Mo3Si ( s )(1)
[0068] 5Mo3O ( s )+4Si ( s )=3Mo5Si3( s )(2)
[0069] 5Mo ( s )+3Si ( s )=Mo5Si3( s )(3)
[0070] Mo5Si3( s )+7Si ( s )=5MoSi2( s )(4)
[0071] Mo ( s )+2Si ( s )=MoSi2( s )(5)
[0072] Mo3Si ( s )+5Si ( s )=3MoSi2 (s )(6)
[0073] When the furnace temperature t≥ 1410℃ (melting point of Si), solid silicon turns into liquid silicon. At this temperature, the reactants can also be converted into the target MoSi2. The reaction process is as follows:
[0074] 3Mo ( s )+Si( l )=Mo3Si ( s )(7)
[0075] 5Mo3O ( s )+4Si( l )=3Mo5Si3 (s )(8)
[0076] 5Mo ( s )+3Si(l )=Mo5Si3( s )(9)
[0077] Mo5Si3( s )+7Si( l )=5MoSi2( s )(10)
[0078] Mo ( s )+2Si( l )=MoSi2( s )(11)
[0079] Mo3Si ( s )+5Si( l )=3MoSi2( s )(12)
[0080] According to the phase formation analysis in the above different temperature ranges, the target MoSi2 can be obtained when the temperature in the furnace is greater than or equal to 1150°C.
[0081] MoSi x The oxygen in the material exists in the form of free oxygen and / or combined oxygen, which mainly comes from the oxygen in the raw silicon powder and / or molybdenum powder, and the oxidation reaction caused by contact with oxygen in the air during the preparation process.
[0082] The oxygen element in the molybdenum-silicon mixture can combine with silicon to form volatile SiO under high temperature treatment. The molybdenum-silicon powder or MoSi can be reduced by removing the gaseous SiO under vacuum conditions. x The oxygen content of the alloy, the reaction mechanism is as follows (a) and (b):
[0083] 2Si ( s ) + O2( g ) = 2SiO ( g )↑(a)
[0084] Si ( s ) + SiO2( s ) = 2SiO ( g )↑(b)
[0085] According to the Gibbs free energy formula of the reaction:
[0086] ΔG=A+BT+RTln(P / Pθ) 2 (c)
[0087] In formula (c), ΔG is the change in Gibbs free energy of the reaction. When ΔG < 0, the reaction can occur. T is the heat treatment temperature. R is the ideal gas constant, which is 8.314 J·mol-1 ·K -1 ; P is the reaction pressure; Pθ is the standard pressure; A and B are constants related to the reaction. Under the conditions of 25℃~1410℃, for formula (a): A is -208400 J·mol -1 , B takes -165.02 J·mol -1 ·K -1 ; For formula (b): A is 698700 J·mol -1 , B takes -340.75 J·mol -1 ·K -1 .
[0088] Calculations show that for formula (a), within the range of 25°C to 1410°C, ΔG < 0, the reaction can proceed spontaneously; for formula (b), when ΔG = 0, formula (c) can be converted into formula (d).
[0089] T=(-A) / [B+2Rln(P / Pθ)](d)
[0090] When the vacuum degree of the reaction is 1×10 -2 Pa, it is calculated that the critical temperature for the reaction is 875 °C, that is, only when the temperature is 875 °C~1410 °C, the two deoxygenation reactions represented by formula (a) and formula (b) can proceed simultaneously.
[0091] Therefore, the phase formation analysis and oxygen reduction thermodynamic analysis in different temperature ranges are comprehensively considered: when the temperature is greater than or equal to 1150℃, the molybdenum-silicon mixture can be fully alloyed into the MoSi2 phase, and the molybdenum-silicon compound phase in the product has only MoSi2 single phase, and no Mo element remains; when the temperature is between 875℃ and 1410℃, the free oxygen and combined oxygen in the furnace can be converted into gaseous SiO for removal, thereby reducing the MoSi x Oxygen content of the material. In summary, the sintering temperature is finally selected between 1150℃ and 1410℃. Within this temperature range, the molybdenum-silicon alloying reaction can be fully realized to obtain the MoSi2 single molybdenum-silicon compound phase material, and the purpose of reducing oxygen can be achieved. At the same time, sintering at a relatively low temperature can avoid the volatilization of silicon at high temperature, save energy and reduce production costs.
[0092] In the embodiment of the present application, when the holding time MoSi is reached x After sintering is completed, shut down the vacuum sintering equipment and cool it down. x The material was taken out after cooling down to room temperature in the furnace.
[0093] In step S103, the crushing method is mechanical crushing, which may be, but is not limited to, any one or more combinations of ball milling, vibration milling, air flow milling, and impact milling.
[0094] In the implementation mode of the present application, MoSi x The block is crushed to a particle D50 size of 2μm-20μm, and [(D90-D10) / D50]≤2.5, which can take into account the lower oxygen content while obtaining the smallest possible powder particle size, which can better control the uniformity of the subsequent preparation of the molybdenum silicon target and improve the yield of the molybdenum silicon compound film in the subsequent target sputtering film forming process. For example, the D50 particle size can be but not limited to 2μm, 3μm, 4μm, 5μm, 7μm, 8μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, and the value of [(D90-D10) / D50] can be but not limited to 0.5, 1, 1.5, 2, 2.5. Among them, the D10, D50, and D90 particle sizes are measured using a laser particle size analyzer. MoSi with smaller particle size and smaller [(D90-D10) / D50] x Powder is conducive to the preparation of molybdenum silicon target with more uniform structure and composition. x The reduction in powder particle size is usually accompanied by more intense mechanical action and more complete contact with oxygen, which may intensify the degree of oxidation of the powder and thus increase the oxygen content of the powder. x The preparation method of the powder can realize degassing and oxygen reduction by vacuum sintering at a suitable temperature and vacuum degree, and at the same time crush it to a suitable particle size, so that MoSi x The powder has a small particle size while still maintaining a low oxygen content. In some embodiments, in order to better reduce the MoSi x The oxygen content of the powder is x The block is crushed to a particle size of 5 μm to 20 μm. In some embodiments, the value of [(D90-D10) / D50] is 0.5-2.5. In some embodiments of the present application, MoSi x The block is crushed to particles with a D50 diameter of 5 μm-12 μm, and [(D90-D10) / D50]≤1.2. In some embodiments, a protective gas such as nitrogen can be used during the crushing process.
[0095] In the embodiment of the present application, the MoSi obtained after crushing x The purity of the powder is ≥99.999% and the oxygen content is ≤1500ppm. xThe purity of the powder may be 99.9991% (5N1), 99.9992% (5N2), 99.9993% (5N3), 99.9994% (5N4), 99.9995% (5N5), 99.9996% (5N6), 99.9997% (5N7), 99.9998% (5N8), 99.9999% (6N). In some embodiments, the oxygen content is ≤1400ppm. In some embodiments, the oxygen content is ≤1300ppm. In some embodiments, the oxygen content is ≤1200ppm. In some embodiments, the oxygen content is ≤1100ppm. In some embodiments, the oxygen content is ≤1000ppm. In some embodiments, the oxygen content is ≤900ppm. In some embodiments, the oxygen content is ≤800ppm. In some embodiments, the oxygen content is ≤700ppm.
[0096] In the implementation mode of the present application, MoSi x The powder may also contain a very small amount of other impurity elements, which may be, but are not limited to, carbon, iron, aluminum, nickel, and copper, wherein the carbon content is ≤200ppm, the iron content is ≤5ppm, the aluminum content is ≤5ppm, the nickel content is ≤5ppm, and the copper content is ≤5ppm. In some embodiments, the carbon content is ≤150ppm; in some embodiments, the carbon content is ≤100ppm; in some embodiments, the carbon content is ≤50ppm; in some embodiments, the carbon content is ≤30ppm; in some embodiments, the carbon content is ≤20ppm; in some embodiments, the carbon content is ≤10ppm.
[0097] Among them, MoSi x The purity of the powder can be detected by high resolution glow discharge mass spectrometry (HR-GDMS); the oxygen content can be detected by oxygen, nitrogen and hydrogen (ONH) analyzer; the impurity element content can be detected by high resolution glow discharge mass spectrometry (HR-GDMS) or inductively coupled plasma mass spectrometry (ICP-MS); MoSi x The crystal phase composition of the powder can be analyzed by XRD.
[0098] The MoSi provided in the embodiments of the present application x The method for preparing the powder comprises mixing silicon powder and molybdenum powder and then sintering them in vacuum. During the vacuum sintering process, the appropriate temperature is controlled to achieve degassing and oxygen reduction while achieving the molybdenum-silicon alloying reaction. Finally, the sintered MoSi x The block is crushed into powder of suitable particle size, and high-purity, low-oxygen content, fine-particle MoSi x Powder. MoSi in the embodiment of the present application x The powder preparation method can adjust the dosage ratio of molybdenum powder and silicon powder according to different molybdenum-silicon atomic ratio requirements, so as to obtain MoSi with different molybdenum-silicon ratios to meet different application requirements.x Powder, and then prepare molybdenum-silicon targets with different molybdenum-silicon ratios.
[0099] The present application also provides a MoSi x Powder, the MoSi x The powder is made of the MoSi x The powder is prepared by the method of preparing the powder. x Powder purity ≥99.999%, oxygen content ≤1500ppm, D50 particle size 5μm-20μm, [(D90-D10) / D50]≤2.5). MoSi x The carbon content of the powder is ≤200ppm, the iron content is ≤5ppm, the aluminum content is ≤5ppm, the nickel content is ≤5ppm, and the copper content is ≤5ppm. x The XRD spectrum of the powder shows that the molybdenum silicon compound phase has only a single phase of MoSi2. When x is greater than 2, the XRD spectrum shows that there is also a Si phase. x The acquisition of MoSi2 single phase powder mainly depends on the vacuum sintering process and the temperature control during the vacuum sintering process. The impurity content mainly depends on the purity of the raw materials and the control of the powder making process. The oxygen content mainly depends on the oxygen isolation and deoxidation technology of the preparation process. Finally, the powder with the smallest possible D50 particle size is obtained while ensuring the low oxygen content. x The powder has the advantages of high purity, low oxygen content, and small particle size. x The molybdenum-silicon target material made of powder has high purity, low oxygen content, low impurity content, high density and uniform structure. It can improve the quality of the molybdenum-silicon compound film deposited by it and enhance the stability of the phase difference between the phase shift film and the exposure light source, thereby improving the contrast and resolution of the exposure pattern under edge scattering.
[0100] The present invention also provides a method for preparing a molybdenum-silicon target, which comprises the following steps:
[0101] (1) Using the MoSi x MoSi powder preparation method x Powder;
[0102] (2) Using the MoSi obtained in step (1) x The powder is pressed into shape to obtain a molybdenum-silicon target.
[0103] Since the MoSi prepared in the above-mentioned embodiment of the present application is used xThe powder is used as the raw material of the target material, so the molybdenum-silicon target material obtained accordingly also has the advantages of high purity, low oxygen content, and dense uniformity, which can meet the quality requirements of the fine electronics industry for molybdenum-silicon targets. Compared with the existing technology of sintering molybdenum powder and silicon powder in one step to obtain molybdenum-silicon targets, the uniformity of molybdenum-silicon targets can be significantly improved. Moreover, the preparation method of the molybdenum-silicon target material of the embodiment of the present application can adjust the dosage ratio of molybdenum powder and silicon powder according to different molybdenum-silicon ratio requirements, thereby obtaining molybdenum-silicon targets with different molybdenum-silicon ratios that meet different application requirements.
[0104] In some embodiments of the present application, step (2) may be to use the MoSi obtained in step (1) x The powder is directly pressed into shape to obtain a molybdenum-silicon target.
[0105] In some embodiments of the present application, when the MoSi2 powder is prepared in step (1), step (2) can be to mix the MoSi2 powder with a certain amount of silicon powder according to the target molybdenum-silicon atomic ratio of the molybdenum-silicon target to obtain a mixed powder, and then press and mold it to obtain a molybdenum-silicon target.
[0106] In some embodiments of the present application, the method of pressing the target powder to obtain the molybdenum-silicon target includes any one of isostatic pressing and hot pressing.
[0107] Isostatic pressing may include hot isostatic pressing, which is the isostatic pressing and sintering of target powder under high temperature and high pressure. Before the hot isostatic pressing process, the target powder can be densified by cold pressing to ensure that the gap between the target powders does not change much during the hot isostatic pressing process, and to ensure that the hot isostatic pressing pressure can always be stably and effectively transmitted to each part of the target, thereby improving the density and microstructure uniformity of the formed molybdenum silicon target.
[0108] Hot pressing molding may include vacuum hot pressing sintering molding. Vacuuming can isolate the air and promptly remove the adsorbed oxygen or gaseous oxides generated by the reaction. In this process, a pressure head can also be set to seal the target powder to avoid thermal expansion of the target powder during sintering, which may lead to problems such as increased target volume and reduced density.
[0109] Accordingly, the present invention also provides a molybdenum silicon target material, using the MoSi target material described above in the present invention. x The powder is prepared, or the molybdenum-silicon target material is prepared by the above-mentioned preparation method.
[0110] The present application also provides a molybdenum-silicon compound film, which comprises using physical vapor deposition technology to vaporize the molybdenum-silicon target material provided in the present application, and depositing it on a substrate through vapor phase transport to form the molybdenum-silicon compound film.
[0111] In the embodiments of the present application, the physical vapor deposition technology includes any one of magnetron sputtering, vacuum evaporation, and ion plating. In some embodiments of the present application, the molybdenum silicon target material described above in the present application is used for magnetron sputtering in a protective atmosphere, and the molybdenum silicon target material is bombarded with high-speed argon ions to separate the molybdenum silicon compound from the target material and deposit it on the substrate to form a molybdenum silicon compound film. The molybdenum silicon compound film prepared using the molybdenum silicon target material of the embodiment of the present application has a low oxygen content, a low impurity content, a dense and uniform film layer, no protruding particles on the surface and / or inside of the film, and a strong bonding force with the substrate, which can reduce the risk of adverse effects on subsequent applications. For example, the subsequent application can be, but is not limited to, applied to phase shift masks in patterned development technology.
[0112] The present application also provides a phase-shift mask, which includes a substrate, and a phase-shift film and a light-shielding film stacked on one surface of the substrate. The phase-shift film is arranged on the substrate, and the light-shielding film is stacked on the side surface of the phase-shift film away from the substrate. The phase-shift film includes the aforementioned molybdenum-silicon compound film.
[0113] In some embodiments of the present application, the substrate may be but is not limited to transparent glass, such as quartz glass or soda glass; the shading film may be but is not limited to a metal chromium (Cr) film, and the shading film may adopt any one of a single-layer structure or a stacked structure of two or more layers.
[0114] In some embodiments, the phase-shift mask further comprises a photosensitive material layer disposed on a surface of the light-shielding film away from the substrate. The photosensitive material layer comprises a photoresist material. In some embodiments, the phase-shift mask further comprises an anti-reflection layer disposed between the light-shielding film and the photosensitive material layer. The anti-reflection layer may comprise chromium oxide.
[0115] In some embodiments of the present application, the phase shift mask includes a blank phase shift mask and a phase shift mask with a preset pattern. The blank phase shift mask is a phase shift mask without a preset pattern. The shading film in the preset area of the blank phase shift mask is removed to obtain a phase shift mask with a preset pattern.
[0116] The phase shift mask provided by the present application can be used for patterned development technology. When the substrate wafer production process reaches 0.18μm, due to edge scattering, many gray shadow areas will appear on the developed pattern after exposure, and the pattern is no longer black and white, and the overall contrast and resolution are reduced. In this case, the phase shift mask with a preset pattern in the embodiment of the present application can make the exposed light produce a phase difference of 175°~185°, and then supplemented by a 6%~30% transmittance change, so that the phase of the light passing through the phase shift film is substantially reversed relative to the phase of the light passing through the light shielding film, so that the light passing through the boundary of the phase shift film and the light shielding film due to diffraction phenomenon and bypassing each other to each other's area cancel each other out, so that the light intensity of the boundary is almost zero, thereby reducing edge scattering, reducing the light intensity of the dark field in the light field, and increasing the light intensity of the bright area, so as to correct the contrast and resolution of the developed pattern, and then form a black and white, small and high-precision exposure pattern, improve the accuracy of exposure and the success rate of development, and ultimately improve the process yield of the product.
[0117] In addition, due to the continuous improvement of the patterning process, technicians in the field have found that narrower line widths can determine that the patterning process has higher resolution and contrast. At present, one of the solutions to reduce the line width is to evolve the wavelength of the light used for exposure to a shorter wavelength, so shorter wavelength ultraviolet light (such as 193nm light) has gradually become a commonly used exposure light source in patterning development technology. The molybdenum silicon target material provided in the above application can effectively avoid the generation of particulate matter in the back-end application. The molybdenum silicon compound film coated thereon is dense and uniform, and the film layer has strong bonding force. The phase shift mask provided in the above application contains the molybdenum silicon compound film. In addition to phase shifting medium and long wavelength ultraviolet light, it can also correct the edge scattering of the wafer using short wavelength ultraviolet light (180nm-350nm) as the exposure light source. Its phase difference and transmittance can meet the application requirements in the field of semiconductor preparation.
[0118] The present application also provides a method for preparing a semiconductor device, comprising placing the phase-shift mask with a preset pattern provided in the present application on the semiconductor substrate to be patterned, and transferring the pattern on the phase-shift mask to the semiconductor substrate to be patterned after exposure and development. Finally, a patterned semiconductor substrate can be prepared. The phase-shift film in the phase-shift mask is optically corrected during the exposure process, so that a fine and precise pattern with clear black and white, high contrast and high resolution can be obtained on the semiconductor substrate, and further forming the structure required for the semiconductor device on the substrate to obtain a semiconductor device. Among them, the semiconductor device can be, for example, but not limited to, a chip. In the preparation process of the chip, other functional layers can be prepared after the patterning process is completed.
[0119] In some implementations of the present application, the semiconductor device can be used in terminal devices, such as mobile phones, tablet computers, laptop computers, digital cameras, wearable electronic devices, virtual reality devices, etc.
[0120] The technical solution of the present application is further described below with multiple embodiments.
[0121] Example 1
[0122] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:2, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0123] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After Pa, the heating system was started, and the vacuum sintering furnace was heated at 5°C / min. After the temperature in the furnace rose to 1250°C, it was kept warm for 3 hours. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain a MoSi2 block.
[0124] S103: crushing the MoSi2 block obtained in S102 into powder particles with a D50 of 8.75 μm and [(D90-D10) / D50]=1.45 by a crusher, i.e. obtaining MoSi2 powder, and using nitrogen for protection during the crushing process;
[0125] S104: The MoSi2 powder obtained in S103 is loaded into a graphite mold, and the temperature is raised to 1250°C at 5°C / min using a vacuum hot pressing sintering furnace, and the pressure is increased to 30 MPa, and the temperature and pressure are maintained for 3 hours to complete the sintering to obtain a molybdenum silicon target.
[0126] Example 2
[0127] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:2, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0128] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After Pa, the heating system was started, and the vacuum sintering furnace was heated at 5°C / min. After the temperature in the furnace rose to 1350°C, it was kept warm for 3 hours. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain a MoSi2 block.
[0129] S103: crushing the MoSi2 block obtained in S102 into powder particles with a D50 of 8.91 μm and [(D90-D10) / D50]=1.64 using a crusher, i.e. obtaining MoSi2 powder, and using nitrogen for protection during the crushing process;
[0130] S104: Same as Example 1.
[0131] Example 3
[0132] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:2.7, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0133] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After 30 0.05 Pa, the heating system was started, and the vacuum sintering furnace was heated at 5 °C / min. After the temperature in the furnace rose to 1250 °C, it was kept warm for 3 h. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain MoSi 2.7 Block;
[0134] S103: The MoSi obtained in S102 2.7 The block was crushed into powder particles with D50 of 9.13 μm and [(D90-D10) / D50]=1.3 by a crusher, i.e. MoSi2 powder was obtained, and nitrogen was used for protection during the crushing process;
[0135] S104: Same as Example 1.
[0136] Example 4
[0137] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:7, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0138] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After Pa, the heating system was started, and the vacuum sintering furnace was heated at 5°C / min. After the temperature in the furnace rose to 1250°C, it was kept warm for 3 hours. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain a MoSi7 block.
[0139] S103: crushing the MoSi7 block obtained in S102 into powder particles with a D50 of 7.89 μm and [(D90-D10) / D50]=1.37 using a crusher, i.e. obtaining MoSi7 powder, and using nitrogen for protection during the crushing process;
[0140] S104: Same as Example 1.
[0141] Comparative Example 1
[0142] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:2, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0143] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After Pa, the heating system was started, and the vacuum sintering furnace was heated at 5°C / min. After the temperature in the furnace rose to 1100°C, it was kept warm for 3 hours. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain a MoSi2 block.
[0144] S103: crushing the MoSi2 block obtained in S102 into powder particles with a D50 of 9.03 μm and [(D90-D10) / D50]=1.6 by a crusher, i.e. obtaining MoSi2 powder, and using nitrogen for protection during the crushing process;
[0145] S104: Same as Example 1.
[0146] Comparative Example 2
[0147] S101: Molybdenum powder and silicon powder are taken according to the atomic ratio of molybdenum to silicon = 1:7, the purity of the molybdenum powder is 99.999%, and the D50 particle size is 6μm (Fisher particle size); the purity of the silicon powder is 99.9996%, and the D50 particle size is 20μm (laser particle size); the molybdenum powder and silicon powder are loaded into the mixing barrel of the mixer, and grinding balls are added at the same time, nitrogen is filled, and the mixer is started at a speed of 10r / min. The molybdenum powder and silicon powder are mixed for 4h until they are uniform, and a molybdenum-silicon mixture is obtained;
[0148] S102: The molybdenum-silicon mixture obtained in S101 is placed in a crucible. After the surface of the molybdenum-silicon mixture is leveled, the crucible is placed in a vacuum sintering furnace, the furnace door is closed, and the vacuum pump is turned on. When the vacuum degree reaches 1×10 -3 After Pa, the heating system was started, and the vacuum sintering furnace was heated at 5°C / min. After the temperature in the furnace rose to 1250°C, it was kept warm for 3 hours. The vacuum was continuously drawn during the sintering process. After the sintering was completed, the furnace was stopped, and the crucible was taken out after cooling to room temperature with the furnace to obtain a MoSi7 block.
[0149] S103: crushing the MoSi7 block obtained in S102 into powder particles with a D50 of 8.12 μm and [(D90-D10) / D50]=2.61 by a crusher, i.e. obtaining MoSi7 powder, and using nitrogen for protection during the crushing process;
[0150] S104: Same as Example 1.
[0151] The MoSi in Examples 1-4 and Comparative Examples 1-2 were analyzed by GDMS, oxygen and nitrogen analyzer, and XRD. x The physical properties of the powder were analyzed, and the results are shown in Table 1:
[0152] Table 1
[0153]
[0154] As shown in Table 1, the MoSi prepared in Examples 1-4 of the present application is prepared by vacuum sintering molybdenum powder and silicon powder with different molybdenum-silicon atomic ratios at a sintering temperature of 1150°C-1410°C. x Block, high purity, low oxygen content, low carbon content; MoSi made by vacuum sintering xThe block is then crushed and pulverized to obtain MoSi with a smaller D50 particle size and particle size distribution. x The purity of the powder is slightly reduced, the oxygen content is significantly increased, and the carbon content is slightly increased. Although the mechanical crushing process makes MoSi x The oxygen content of the material has increased, but it can be seen that the MoSi obtained in Examples 1-4 x The powder has a small particle size and still has a low oxygen content. x The molybdenum silicon compound phase of the powder only has a single phase of MoSi2. Specifically, the phase composition of the MoSi2 powder obtained in Examples 1-2 only includes a single phase of MoSi2; the phase composition of the MoSi2 powder obtained in Examples 3-4 only includes a single phase of MoSi2. 2.7 The phase composition of MoSi7 powder only includes MoSi2 phase and Si phase.
[0155] Comparing Example 1 with Comparative Example 1, Comparative Example 1 was sintered at 1100°C, and the oxygen content and carbon content of the MoSi2 block and MoSi2 powder prepared were significantly increased compared with Example 1, with significant differences; the phase composition of the MoSi2 powder included not only the MoSi2 phase, but also the Mo5Si3 impurity phase. This also shows that the vacuum sintering process at a suitable temperature in Example 1 of the present application significantly reduced the oxygen content in the MoSi2 powder, while avoiding the presence of other molybdenum silicon compound impurity phases.
[0156] Figure 1 For MoSi in Examples 1-4 and Comparative Examples 1-2 of the present application x The X-ray diffraction analysis (XRD) result of the powder. Figure 1 It can be seen that the phase composition of the MoSi2 powder of Examples 1-2 only includes a single phase of MoSi2, with no residual molybdenum phase and silicon phase, and no other molybdenum-silicon compound impurities; 2.7 The phase composition of MoSi7 powder only includes MoSi2 phase and Si phase, does not contain molybdenum phase, and has no other molybdenum silicon compound impurities. The MoSi2 powder phase of Comparative Example 1 includes not only MoSi2 phase but also Mo5Si3 impurity phase. The presence of impurity phase will further react in the subsequent preparation process of molybdenum silicon target, resulting in uneven organization of molybdenum silicon target and reducing the quality of molybdenum silicon target.
[0157] Figure 2A This is a scanning electron microscope (SEM) image of the molybdenum silicon target material prepared in Example 4. Figure 2B This is an EDS energy spectrum scan of the molybdenum silicon target prepared in Example 4; Figure 3A This is a scanning electron microscope (SEM) image of the molybdenum silicon target prepared in Comparative Example 2. Figure 3B This is the EDS spectrum scan of the molybdenum silicon target prepared in Comparative Example 2. Figure 2A and Figure 3A , Figure 2B and Figure 3B It can be seen that Example 4 obtained a molybdenum-silicon target with uniform structure, while the molybdenum-silicon target of Comparative Example 2 had an uneven internal structure.
[0158] In the embodiment of the present application, high-purity molybdenum powder and silicon powder are mixed under a protective atmosphere, vacuum sintered, and the vacuum sintering temperature is controlled to achieve an alloying reaction of a single molybdenum-silicon compound phase of MoSi2, and deoxidation is achieved at the same time to ensure that the oxygen content in the product is at a low level, and finally MoSi2 with high purity, low oxygen content and fine particle size is obtained. x Powder can improve the quality of downstream products such as molybdenum silicon targets and semiconductor devices.
[0159] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.
[0160] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0161] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, and c can be single or multiple.
[0162] In this application, “~” or “-” represents a range value, including the endpoint values at both ends. For example, the value of a can be 0.5~15, which means that the value of a can be between 0.5 and 15, and includes the endpoint values 0.5 and 15.
[0163] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
Claims
1. A MoSi x The method for preparing a powder is characterized in that: include: Molybdenum powder and silicon powder are mixed according to the atomic ratio of molybdenum to silicon of 1:x to obtain a molybdenum-silicon mixture; wherein x≥2; The molybdenum-silicon mixture is placed in a vacuum sintering device for vacuum sintering to obtain MoSi x The block, the sintering temperature of the vacuum sintering is 1150°C-1410°C; the vacuum sintering process is continuously vacuumed; The MoSi x The block is crushed to a particle size of 2 μm-20 μm at D50, and [(D90-D10) / D50]≤2.5 to obtain MoSi x Powder.
2. MoSi as claimed in claim 1 x The method for preparing a powder is characterized in that: The vacuum degree of the vacuum sintering is 1×10 -3 Pa ~1Pa, and the vacuum sintering includes keeping the sintering temperature at the sintering temperature for 1h~5h.
3. MoSi as claimed in claim 2 x The method for preparing a powder is characterized in that: During the vacuum sintering process, the temperature is raised to the sintering temperature at a heating rate of 1°C / min to 10°C / min.
4. MoSi as claimed in claim 1 x The method for preparing a powder is characterized in that: The purity of the molybdenum powder is ≥99.999%, and the particle size of the Fisher particle size D50 is 1 μm to 10 μm; the purity of the silicon powder is ≥99.999%, and the particle size of the laser particle size D50 is 10 μm to 100 μm; and the mixing is carried out under a protective atmosphere.
5. MoSi as claimed in claim 1 x The method for preparing a powder is characterized in that: The MoSi x The blocks are crushed to particles with a D50 particle size of 5 μm-12 μm, and [(D90-D10) / D50]≤1.
5.
6. MoSi as claimed in claim 1 x The method for preparing a powder is characterized in that: The crushing method includes any one or more combinations of ball milling, vibration milling, air flow milling and impact milling.
7. MoSi according to claim 1 x The method for preparing a powder is characterized in that: The MoSi x The purity of the powder is ≥99.999%, and the oxygen content is ≤1500ppm.
8. MoSi as claimed in claim 1 x The method for preparing a powder is characterized in that: The MoSi x The carbon content of the powder is ≤200ppm, the iron content is ≤5ppm, the aluminum content is ≤5ppm, the nickel content is ≤5ppm, and the copper content is ≤5ppm.
9. A MoSi x The powder is characterized by: The MoSi x The D50 particle size of the powder is 2 μm-20 μm, and [(D90-D10) / D50]≤2.
5. x The purity of the powder is ≥99.999%, and the oxygen content is ≤1500ppm.
10. MoSi according to claim 9 x The powder is characterized by: The MoSi x The carbon content of the powder is ≤200ppm, the iron content is ≤5ppm, the aluminum content is ≤5ppm, the nickel content is ≤5ppm, and the copper content is ≤5ppm.
11. A method for preparing a molybdenum-silicon target, characterized in that: include: Using the MoSi according to any one of claims 1 to 8 x MoSi powder preparation method x Powder or MoSi according to claim 9 or 10 x The powder is pressed into shape to obtain a molybdenum-silicon target.
12. The method for preparing a molybdenum-silicon target according to claim 11, characterized in that: The press molding includes any one of isostatic pressing and hot pressing.
13. A molybdenum-silicon target, characterized in that: Using the MoSi according to any one of claims 9 to 10 x The powder is prepared or obtained by the preparation method described in any one of claims 11-12.
14. A molybdenum-silicon compound film, characterized in that: The molybdenum-silicon target material as claimed in claim 13 is obtained by physical vapor deposition.
15. A phase shift mask, characterized in that: It comprises a substrate and a phase shift film and a light shielding film stacked on one surface of the substrate, wherein the phase shift film comprises the molybdenum silicon compound film as claimed in claim 14; and the phase shift mask comprises a blank phase shift mask or a phase shift mask with a preset pattern.
16. A method for preparing a semiconductor device, characterized in that: include: Placing the phase-shift mask having a preset pattern as claimed in claim 15 on a semiconductor substrate to be patterned; After exposure, the preset pattern on the phase-shift mask having the preset pattern is transferred to the semiconductor substrate to be patterned.
Citation Information
Patent Citations
Refractory metal silicide target, its manufacturing method, refractory metal silicide thin film and semiconductor device
JP2896233B2